Short-Term Survival and Prognostic Factors in Cervical Cancer Patients Requiring Hemodialysis: A Retrospective Cohort Study - Bundjali, Muhammad Trihatmowijoyo; Marbun, Maruhum Bonar Hasiholan; Rajabto, Wulyo; Rinaldi, Ikhwan; Shatri, Hamzah; Partiningrum, Dwi Lestari; Makmun, Dadang; Nugroho, Pringgodigdo; Koesnoe, Sukamto; Soewondo, Pradana (UI Scholars Hub, 2026)
Cervical cancer is a common gynecological malignancy, particularly in developing countries, where it coexists with renal impairment in over one-third of patients. This disease typically presents acutely and progresses rapidly. Consequently, kidney replacement therapy, including hemodialysis (HD), is commonly required. To assess survival rates and associated factors, this retrospective cohort study analyzed the medical records of 252 cervical cancer patients who began HD across a three-month follow-up period. Kaplan–Meier analysis indicated a median short-term survival duration of 71.5 days (range: 7–90), with 1-, 2-, and 3-month survival rates of 56%, 51%, and 49%, respectively. Multivariate Cox regression identified post-HD systolic blood pressure <110 mmHg (hazard ratio [HR] 3.354; 95% confidence interval [CI]: 2.346–4.795; p-value <0.001) and interdialytic weight gain ≥5% (HR 1.685; 95% CI: 1.125–2.521; p-value <0.011) as significant predictors of decreased survival. Other variables, including age, urea, albumin, vascular access, baseline creatinine, and cancer stage, were not significantly associated with short-term survival. These findings underscore the critical role of salt and fluid management, adherence to dietary and dialysis regimens, and close monitoring of weight in improving outcomes. Interventions targeting modifiable factors may improve the survival of cervical cancer patients who require HD. Such approaches, therefore, warrant further investigation.